THD ANALYSIS IN THREE PHASE-THREE LEVEL VSI WITH MPPT TRACKER AND SEPIC CONVERTER FOR SOLAR PV ARRAY - Saranya, S.K.; Raj, T.Gowtham; Ranjani, P. (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
This paper deals with the analysis of total harmonic distortion in three phase three level voltage source inverter (VSI) for the solar photovoltaic array. The Voltage source inverter as used in high power applications here we are using for the Renewable Energy as Application. The result for the Voltage Source Inverter will be quasi square wave or square wave. The Harmonics will be high if we are using the low level inverter. The 1200 or 1800 are the two modes of operation for voltage source inverter and its choose based upon its application. The MPPT technique is used to get the maximum power from the Solar PV. The SEPIC converter is DC-DC converter in which it can operates either buck or boost modes and it eliminates the ripples by using the filter. In order to improve the efficiency the SEPIC and Perturb and Observe Technique is used. The focus of the paper is to analyze and reduce the Total Harmonic Distortion with the MPPT Technique and DC-DC converter and its connected to the Grid. The simulation results for the paper and the THD values are calculated for voltage source inverter (VSI) are given below [13], [14].